2009
DOI: 10.3999/jscpt.40.59
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Cranberry Juice on Phenytoin Metabolism by Human Liver Microsomes

Abstract: CYP2C9 is involved in the metabolism of many drugs such as warfarin and phenytoin(PHT). It is well known that some foods cause pharmacokinetic alterations of drugs and lead to toxicity. Regarding the interaction caused by cranberry juice(CrJ), its influence on the metabolism of warfarin, a CYP2C9 substrate, is controversial. In addition, information concerning the influence of CrJ on the pharmacokinetics of other substrate drugs of CYP2C9 is not available. To examine the inhibitory effect of CrJ on the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(14 reference statements)
2
4
0
Order By: Relevance
“…In this study, CrJ also concentration‐dependently inhibited diclofenac metabolism, and the IC 50 value was estimated to be 1.44%. Previously, we found that phenytoin metabolism was suppressed by CrJ in human liver microsome assay [9]. These observations support the hypothesis that CrJ inhibits the metabolism of CYP2C9 substrates.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In this study, CrJ also concentration‐dependently inhibited diclofenac metabolism, and the IC 50 value was estimated to be 1.44%. Previously, we found that phenytoin metabolism was suppressed by CrJ in human liver microsome assay [9]. These observations support the hypothesis that CrJ inhibits the metabolism of CYP2C9 substrates.…”
Section: Discussionsupporting
confidence: 85%
“…In a previous in vitro study, CrJ inhibited the hydroxylation of flurbiprofen, a CYP2C9 substrate, to approximately 50% by human liver microsomes [8]. We also found that CrJ significantly inhibited the metabolism of phenytoin, another CYP2C9 substrate, in vitro [9]. Therefore, it is anticipated that CrJ inhibits CYP2C9‐mediated drug metabolism in vivo .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…These observations were also confirmed by an in vivo study (Uesawa and Mohri, ). Cranberry juice was found to diminish CYP2C9 activity versus diclofenac and phenytoin in human liver microsomes, although this occurrence was not observed clinically (Ushijima et al ., ; Ushijima et al ., ). In addition to the isoforms 3A4 and 2C9, anthocyanins and their aglycones were found to possess weak inhibitory activity on CYP2D6 although 1000‐fold lower with respect to grapefruit‐derived furanocoumarins; on the basis of this observation, interference with drug metabolism by CYP2D6 is highly unlikely (Dreiseitel et al ., ).…”
Section: Drug Interactionsmentioning
confidence: 98%
“…Cranberry can inhibit CYP2C9 and 3A4, therefore it can theoretically interact with ACDs that are substrates of these isozymes (Table 1). In vitro studies have shown cranberry juice to inhibit CYP2C9-mediated metabolism of phenytoin (Ushijima et al, 2009a). Furthermore, the international normalized ratios of warfarin, another CYP2C9 substrate, were shown to be elevated in numerous case reports (Grant, 2004;Griffiths et al, 2008;Hamann et al, 2011;Paeng et al, 2007;Suvarna et al, 2003;Welch and Forster, 2007).…”
Section: Cranberrymentioning
confidence: 99%